A selector-combiner circuit for multi-pixel CMOS photon detector - Chuah, J.H.; Holburn, D. (Taylor & Francis, 2015)
This paper presents a selector-combiner (SC) circuit for use as a constituent block for a multi-pixel complementary metal-oxide-semiconductor (CMOS) photon detector. The circuit essentially allows signal from pixels of interest to be summed and output. This pixel-selection configurability may enhance imaging performance and also produce different imaging effects for various analyses. A 9-to-1 SC circuit was designed and fabricated in an Austriamicrosystems (AMS) 0.35 mu m process technology. The worst-case linear working range at the input was found to be between 1.50 and 1.80V, occurring when all inputs were enabled. It exhibited an insignificant signal loss of about -0.96dB when all inputs were enabled. The circuit has been proven to achieve a minimum bandwidth of 7.2MHz. Simulated and experimental results have shown that signal addition can be performed effectively and the circuit is suitable to be integrated into a multi-pixel CMOS photon detector.